The Revenge of Baumol's Cost Disease?: Monetary Union and the Rise of Public Sector Wage Inflation - Alison Johnston (London School of Economics and Political Science (LSE), European Institute, 2011)
Many political scientists and economists have addressed the implications of the public sector's sheltered status on their unions' wage strategies vis-à-vis the government. Since the public sector is a monopoly provider of necessary and price inelastic services, conventional wisdom suggests that public sector unions' push for wage increases which their productivity does not merit, exacerbating inflation and fiscal deficits. The argument in this paper challenges this conventional view, and maintains that the recent, puzzling rise in public sector wage inflation, relative to that in manufacturing, in Euro-zone countries is an unintended result of the institutional shift towards European Economic and Monetary Union (EMU). During the 1980s and 1990s, differences in wage inflation between the manufacturing and public sector within most EMU candidate-countries were low. After 1999, these differences significantly worsened; wage moderation continued in the manufacturing sector while wage inflation arose in the public sector. It is argued here that monetary union's predecessors, the European Monetary System and Maastricht regimes, imposed two important constraints on public employers, which enhanced their ability to enforce wage moderation: the commitment to a hard currency policy via participation in the Exchange Rate Mechanism, adopted by some earlier than others and, the Maastricht criteria. Monetary union's removal of these two constraints weakened public employers' capability to deny inflationary wage settlements to public sector unions. Panel regressions results outline a statistically significant relationship between monetary union and higher levels of wage inflation in the public sector, relative to manufacturing. The paper concludes with a brief discussion of the implications of monetary union for inter-sectoral dynamics.
Keywords: 330; Sectoral Interests; Employers; Trade Unions; European Monetary Union; Institutional Change